Dairy Milk Distribution Network and Its Impact on the Income of Dairy Farmers in Wukirsari Village Community, Sleman - Pramono, Didi; Kismini, Elly; Fajar, Fajar; Martanti, Nadia Luki; Fauzi, Lesa; Adiansyah, Darel Viko (Komunitas: International Journal of Indonesian Society and Culture, 2025)
This study aims to explain the distribution network of cow’s milk and its impact on farmers’ income on the slopes of Merapi. The research uses a qualitative approach. The research is located in Wukirsari Village, Cangkringan District, Sleman Regency, Yogyakarta. The subject of this research is the farmer-herder community in the Cangkringan District. The informants consisted of 7 farmers, eight distributors, and three koperasi employees, and the study was conducted for 2 months. The data collection techniques were interviews, observations, and documentation. The validity of the data is tested through source and method triangulation techniques. Data is analyzed qualitatively, including data collection, condensation, presentation, and conclusion. Farmers are assisted by cooperatives in the milk production process, from cow care to milking. The co-operative is a means of supporting the income of dairy farmers. Milk distribution in Wukirsari is carried out by cooperatives to milk agents, milk processing industries, culinary milk, and directly to consumers. Farmers’ income in Wukirsari depends on the daily milk farmers’ deposit or value. However, the income is still insufficient to meet the needs because the cost of cow care and cow feed cuts it. Therefore, farmers make up for the lack of needs with part-time jobs such as collecting wood, selling calves, and selling grass.